Effects of a 12-week training programme on selected hormonal and psychological parameters and their interrelationships in highly-trained male and female swimmers - Surała, Olga; Malczewska-Lenczowska, Jadwiga; Turowski, Dariusz; Słomiński, Paweł; Certa, Maciej; Crewther, Blair T (Biology of Sport, 2025)
Swimming training load (TL) is regarded as a major stimulus for hormonal adaptation, but research findings are inconsistent. Methodological limitations also exist (e.g., cross-sectional sampling) with little knowledge of acute hormone responses and hormone-psychological interactions that regulate training outputs. These issues were addressed in a 12-week training study on highly-trained swimmers. Eighteen swimmers (10 males, 8 females) completed a 12 week training programme, involving a stepwise reduction in TL before a major competition. Testing was conducted from Monday–Friday at week one (T1), week five (T2), and week 12 (T3), including measures of salivary testosterone and cortisol, willingness to train, stress, and sleep quality. Post-session hormones were assessed on Mondays and Fridays. Daily-averaged swimming distance decreased by -21% (T2) and -57% (T3), relative to T1 ( p < 0.001). We found no significant training effect on the cortisol and testosterone measures, both baseline and acute exercise response, willingness to train, and sleep quality. Only stress varied with training, decreasing significantly at T2 and T3 from T1 in female swimmers. Among male swimmers, daily changes in baseline cortisol and testosterone were related ( r = 0.45) at T1, as was sleep quality and stress ( r = 0.39) at T3. In summary, highly-trained swimmers showed little or no adaptive changes prior to a major competition. The one exception was self reported stress among female swimmers, which decreased along with TL. The emergence of daily interrelationships (in male swimmers only) between selected hormonal or psychological outputs could provide a new lens to assess pre-training preparation.